Differential Expression and Turnover of the Tomato Polyphenol Oxidase Gene Family during Vegetative and Reproductive Development. - Thipyapong, P. (1997)
Polyphenol oxidases (PPOs) are encoded by a highly conserved, seven-member gene family clustered within a 165-kb locus on chromosome 8 of tomato (Lycopersicon esculentum). Using gene-specific probes capable of differentiating between PPO A/C, PPO B, PPO D, and PPO E/F, we examined the spatial and temporal expression of this gene family during vegetative and reproductive development. RNA blots and in situ hybridization using these probes showed that although PPO expression is primarily confined to early stages of development, the steady-state mRNA levels of these genes are subject to complex patterns of spatial and temporal regulation in vegetative and reproductive organs. Young tomato leaves and flowers possess the most abundant PPO transcripts. PPO B is the most abundant in young leaves, whereas in the inflorescence PPO B and E/F transcripts are dominant. Differential expression of PPOs is also observed in various trichome types. PPO A/C are specifically expressed in type I and type IV trichomes. In contrast, PPO D is only expressed in type VI trichomes. Type I, IV, and VI trichomes possess PPO E/F transcripts. Immunolocalization verified the translational activity of PPOs identified by in situ hybridization and suggested cell-type-specific, developmentally programmed PPO turnover. In addition, immunolocalization demonstrated the accumulation of PPO in specific idioblast cells of stems, leaves, and fruits.